PENDEKATAN PARTISIPASI DALAM PEMBANGUNAN RUANG KOMUNAL ANAK: STUDI KASUS DI RW 04 RT 07 KAMPUNG RAWA, JOHAR BARU, JAKARTA PUSAT - jayanti, Theresia; Agnatasya Listianti Mustaram; Irene Syona Darmady; Laura Tri Agustin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2024)
Kampung Rawa, located in Johar Baru District, Central Jakarta, faces a major challenge in terms of limited land available for area development. With a dense population and diverse socio-economic conditions, this area often struggles with a lack of space for housing, public facilities, and areas for social interaction among its residents. The limited land in Kampung Rawa is often underutilized, leading to issues such as slum settlements, a lack of green spaces, and insufficient communal facilities. In this context, innovative architectural design strategies are needed to efficiently use the limited land while also considering the social needs of the community, especially for children's play areas. Approaches such as the design of multifunctional communal spaces on narrow land can be a solution to improving residents' quality of life. Through sustainable and participatory design interventions, the spatial challenges in Kampung Rawa can be addressed by creating an environment that is more friendly, functional, and conducive to social interaction. The